Glukosa Darah dan Kelangsungan Hidup Benih Leptobarbus Hoevenii Pada Sistem Resirkulasi - Febi Febriana Putri; Muhammad Sugihartono; Muarofah Ghofur (Universitas Batangahari Jambi, 2021)
The purpose of this study was to determine the optimal density of jelawat (L. hoevenii Blkr) fry in rearing with a recirculation system. This study used a completely randomized design (CRD) with 4 treatments and 3 replications, where the treatments were: Treatment A: stocking density 5 fish/L, Treatment B: stocking density 10 birds/L, Treatment C: stocking density 15 birds/L and Treatment D : Stocking density of 20 fish/L. Parameters observed were survival, blood glucose and water quality. The results showed that the average blood glucose was 56 mg/dl and the average survival of jelawat fish was 99.62%. The results of water quality measurements show that the temperature ranges from 28.5o-29 oC, water pH ranges from 6.4-6.7, dissolved oxygen ranges from 5-5.4 ppm, carbon dioxide values ranges from 2.1-5.1 ppm, ammonia ranges from 0.0011-0.0018.